2011
DOI: 10.1210/jc.2010-2065
|View full text |Cite
|
Sign up to set email alerts
|

Progestogen-Only Contraceptives and the Risk of Acute Myocardial Infarction: A Meta-Analysis

Abstract: Data from observational studies suggest no increase in risk of MI with POC use. However, these results are based on limited data. Further investigations are needed, especially among women at high MI risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 42 publications
2
15
0
6
Order By: Relevance
“…[19][20][21][22][23] Although arterial events are less common than venous thromboembolism in women of reproductive age, the sequelae of stroke and myocardial infarction may be more devastating than those of venous thromboembolism. A large Danish cohort study found that women aged 45-49 years had 20 times the risk of stroke and 100 times the risk of myocardial infarction as women aged [15][16][17][18][19]. In this cohort, estrogen-containing contraceptive use increased the overall risk of stroke by as much as 2.2 times and of myocardial infarction by as much as 2.3 times.…”
Section: Cardiovascular Eventsmentioning
confidence: 81%
See 1 more Smart Citation
“…[19][20][21][22][23] Although arterial events are less common than venous thromboembolism in women of reproductive age, the sequelae of stroke and myocardial infarction may be more devastating than those of venous thromboembolism. A large Danish cohort study found that women aged 45-49 years had 20 times the risk of stroke and 100 times the risk of myocardial infarction as women aged [15][16][17][18][19]. In this cohort, estrogen-containing contraceptive use increased the overall risk of stroke by as much as 2.2 times and of myocardial infarction by as much as 2.3 times.…”
Section: Cardiovascular Eventsmentioning
confidence: 81%
“…15 Two recent meta-analyses showed no association between progestin-only methods and arterial events. 16,17 Use of estrogen-containing contraceptives increases the risk of venous and arterial thromboembolic events. Other risk factors include, but are not limited to, age, obesity, smoking, diabetes, hypertension, migraine headaches (with or without aura) and thrombogenic mutations.…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…In a large population Swedish prospective study with most of the current OC users taking low-dose estrogen and second-or thirdgeneration progestins, OC use was not associated with an increased risk of MI [39]. Data from observational studies with progestogen-only OCs suggest no increase in MI risk [40].…”
Section: Oral Contraceptionmentioning
confidence: 92%
“…В крупномасштабном швед-ском популяционном проспективном исследова-нии, в котором у большинства женщин, получавших ОК, это были препараты с малыми дозами эстроге-нов и прогестинами второго и третьего поколений, не было найдено ассоциации ОК с повышением риска инфаркта миокарда [484]. Данные обсерваци-онных исследований с применением только проге-стоген-содержащих ОК не выявили повышения риска инфаркта миокарда [485].…”
Section: беременностьunclassified